Analysis of The Supreme Court Ruling 557 K/PDT.SUS-HKI/2015 Related to Intellectual Property Disputes in Indonesia - Muhammad Khusnul Hidayat; Marisa Kurnianingsih (Proceeding International Conference Restructuring and Transforming Law, 2023)
A brand can be thought of as the image of a company or product, and can include elements such as a logo, slogan, colors, sounds, and even scents associated with the brand. One of the trademark cases involved French Cardin, who discovered that the same trademark as his was registered, namely the Pierre Cardin trademark and logo, owned by an Indonesian businessman named Alexander Satryo Wibowo, for the same type of trademark. Class 3 cosmetic products, especially Pierre Cardin perfume. The research uses normative legal research which focuses on legal studies from an internal perspective with the research object focusing on legal norms. To explore the legal issues being researched, several approaches are used, namely the statutory approach, case approach, historical approach and conceptual approach. The Pierre Cardin (France) brand is registered with the Directorate General of Intellectual Property with registration number IDM000192198. Apart from that, the brand was renewed with the number R002008005130 through an extension application submitted by Pierre Cardin, a French citizen, who was authorized to an IPR consultant named Ludiyanto, SH, MH, MM, WNI, from the Drewmarks Intellectual Property Services Office, Jakarta. On December 15 2008. In this decision, the Supreme Court confirmed that the Pierre Cardin mark had been legally registered in Indonesia by Pierre Cardin Indonesia and had received legal protection since its registration in 1997. The registration of the mark had been carried out in accordance with the provisions of the Trademark Law and Geographical Indications, as well as their implementing regulations. Therefore, Pierre Cardin Indonesia has exclusive rights to use the mark in Indonesia.